2018
DOI: 10.3390/su10114096
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, Experiences, and Priorities Supporting Agroecosystem Management Decisions Differ among Agricultural Producers, Consultants, and Researchers

Abstract: The sustainability of agriculture depends as much on the natural resources required for production as it does on the stakeholders that manage those resources. It is thus essential to understand the variables that influence the decision-making process of agricultural stakeholders to design educational programs, interventions, and policies geared towards their specific needs, a required step to enhance agricultural sustainability. This study employed a survey of multiple-choice and open-ended questions to examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…The choice of trainer was also found to be important, with formal personal sources of information and farmers' associations and consultants suggested as being important to involve (Hochman and Carberry 2011). One study reported the importance of inclusion of advisers and researchers with farmers in training (McKenzie et al 2018). Involving others in the family or farm team in training was also found to be important in increasing knowledge and retention of knowledge in farm family health (Brumby et al 2009).…”
Section: Trainingmentioning
confidence: 99%
“…The choice of trainer was also found to be important, with formal personal sources of information and farmers' associations and consultants suggested as being important to involve (Hochman and Carberry 2011). One study reported the importance of inclusion of advisers and researchers with farmers in training (McKenzie et al 2018). Involving others in the family or farm team in training was also found to be important in increasing knowledge and retention of knowledge in farm family health (Brumby et al 2009).…”
Section: Trainingmentioning
confidence: 99%
“…Para el último se resaltan conceptos como Remote-Sensing, en estudios sobre cambio climático, fenómenos atmosféricos y cambios en el uso de la tierra (Verbesselt et al, 2012;Knox et al, 2013;Baudouin et al, 2014;Davies et al, 2016); Model Validation, usado para pronosticar comportamientos de plagas y de cultivos, como también procesos de desarrollo en una comunidad en las actividades agroalimentarias (Crespo et al, 2011;Martínez et al, 2013;Verhoog et al, 2016;Coston et al, 2017). Questionnaire-Survey herramienta de recolección de información primaria en publicaciones con enfoque social, que buscan la percepción comunitaria hacia el uso, manejo y conservación de los ecosistemas (Babai et al, 2015;Ciftcioglu, 2017;Shooshtarian and Rajagopalan, 2017;Acosta et al, 2018;Mckenzie et al, 2018;Nunes et al, 2019;Dang et al, 2019).…”
Section: -2000 2001-2010 2011-2019unclassified